Analisis Pembentukan Portofolio Berbasis Risk dan Return (Studi Kasus Saham di Jakarta Islamic Index Periode Juni 2011 – Mei 2016) - Fitria Yuliani; Noer Azam Achsani (Department of Islamic Economics, IPB University, 2017)
This research goals are to analyze risk and return level of stocks in JII using Markowitz model and single index model, to construct an optimal portfolio, determine the fund proportion, to analyze risk and return generated by optimal portfolio, to formulate managerial implications. The sample are 9 stocks that are listed consistently and did not stock split or reverse stock and the number of observation in 300 stocks during the period June 2011 to May 2016. Construct an optimal portfololio using Markowitz model and single index model. The result shows that the Single Index Model construct 1 portfolio consists of : UNVR (64.2%), LPKR (14.7%), ASRI (9.4%), LSIP (1.4%), INTP (5.8%) and SMGR (4.2%), whereas the Markowitz Model construct 2 portfolio consists of: ASRI (4.52% dan 4.3%), INTP (9.4% dan 8.62%), LSIP (11.64% dan 11.359%), SMGR (25.31% dan 24.059%), and UNVR (49.1% dan 51.649%). This study evidence that construct an optimal portfolio using Single Index Model more efficient than Markowitz Model. Empirical result of this study have implication for investor and the development of the theory an optimal portfolio on JII.